Why air forces fail : the anatomy of defeat - Higham, Robin, 1925-2015; Harris, Stephen John (University Press of Kentucky, 2006)
According to Robin Higham and Stephen J. Harris, "Flight has been part of the human dream for aeons, and its military application has likely been the dark side of that dream for almost as long." In the twentieth century, this dream and its dark side unfolded as the air forces of the world went to war, bringing destruction and reassessment with each failure. Why Air Forces Fail examines the complex, often deep-seated, reasons for the catastrophic failures of the air forces of various nations. Higham and Harris divide the air forces into three categories of defeat: forces that never had a chance